Nurse Retention in the Operating Room After Perioperative Core Curriculum Completion - Vortman, Rebecca; Bergren, Martha; Baur, Karen; Floyd, Valerie (Operating Room Nurses Association of Canada Journal, 2019)
With the cost, in the US, of training one operating room (OR) registered nurse exceeding 50,000 USD (67,073 CAD) retention beyond the first year is a priority. This quality improvement project was conducted at a 500-bed medical center in a mid-west metropolitan area in the United States and incorporated Periop 101 Core- Curriculum modules into the operating room nurse orientation to increase nurse retention. Unless otherwise specified statistics and dollar values in this article are based on the US. One-year retention rates were 59% in the pre-implementation group and 87% after adopting Periop 101 for orientation of newly hired registered nurses. Second year retention rates were 37% in the pre-implementation group and 70% after adopting Periop 101.